Analysis of State-Owned Asset Administration at the North Sulawesi Regional Police - Fidi Pebriyanto; Jenny Morasa (CV. Ulil Albab Corp, 2025)
The administration of State-Owned Assets (BMN) encompasses activities such as bookkeeping, inventory management, and reporting, which are essential to ensuring accountability and efficiency. At the North Sulawesi Regional Police, the administration of BMN is guided by principles of effectiveness, efficiency, and optimal utilization. This research examines the application of the Agency-Level Financial Application System (SAKTI) in facilitating BMN administration within the organization. A qualitative approach was employed, utilizing data collection methods such as observation, interviews, and documentation, followed by descriptive analysis. The findings indicate that the SAKTI system has been implemented in accordance with prevailing regulations; however, challenges persist, particularly in maximizing its operational potential. Key obstacles include insufficient user training and limitations in system integration, which hinder optimal functionality. This study underscores the need for targeted improvements in these areas to enhance the overall efficiency and effectiveness of BMN administration, ensuring better asset utilization and accountability.